China’s Peaceful Rise or Assertive Turn? Evaluating Beijing’s Indo-Pacific Strategy - Ahsan Saeed; Anees Muhammad Khan; Aliza Shahzad (ASIAN Journal of International Peace & Security (AJIPS), 2025)
China’s rapid rise is transforming the regional dynamics in the Indo-Pacific driven by its expanding economic footprint and increasing strategic assertiveness. While China claims that its rise is peaceful, many western scholars and policymakers interpret China’s growing influence as assertive behavior that aims to challenge the rules-based international order. This study challenges the conventional binary between China’s “peaceful rise” narrative and Western perceptions of hegemonic ambition by analyzing through the lens of English School of Thought. The research qualitative and analytical in nature, relying mainly on secondary sources. The research finds that China’s strategy is deliberate synthesis of economic development and strategic assertiveness that reflects key assumptions of the English School. On one hand, China projects a peaceful image rooted in interdependence and shared norms through BRI and broader global economic integration. On the other hand, its security architecture reveals an assertive drive to safeguard interests and reshape regional hierarchies that aligns with the English School’s notion of international society, where states operate within a network of shared norms and rules while pursuing self-interest. This dual-track approach makes China’s rise both cooperative and competitive, challenging simplistic characterizations and underscoring the complexity of Beijing’s Indo-Pacific engagement.